2023
DOI: 10.3390/ijerph20064994
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Health Coaching in Smoking Cessation and Promoting the Use of Oral Smoking Cessation Drugs in Patients with Type 2 Diabetes: A Randomized Controlled Trial

Abstract: Introduction: This study looked into the effectiveness of a 6 month health coaching intervention in smoking cessation and smoking reduction for patients with type 2 diabetes. Methods: The study was carried out via a two-armed, double-blind, randomized-controlled trial with 68 participants at a medical center in Taiwan. The intervention group received health coaching for 6 months, while the control group only received usual smoking cessation services; some patients in both groups participated in a pharmacothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“… 27 The feasibility and acceptability assessment of a proposed diabetes-specific smoking cessation intervention for undertaking a future large-scale randomised controlled trial is particularly advisable in view of the reported low recruitment, uptake and challenges encountered in two recent smoking cessation trials carried out among individuals with DM. 28 29 These trials, which were initiated before the COVID-19 pandemic, in 2018, 28 and after the declaration of the pandemic, in August 2020, 29 did not reach the target sample size and were later terminated due to lack of funding, 28 and following the recall of varenicline which was one element of the study intervention, 29 respectively. Conducting a feasibility study will help estimate the recruitment rate and study uptake, identify potential challenges (along with mitigating factors) and assure the intervention’s acceptability among patients and providers a priori, thus ensuring that the main trial targets can be met before proceeding with a larger, definitive trial.…”
Section: Introductionmentioning
confidence: 99%
“… 27 The feasibility and acceptability assessment of a proposed diabetes-specific smoking cessation intervention for undertaking a future large-scale randomised controlled trial is particularly advisable in view of the reported low recruitment, uptake and challenges encountered in two recent smoking cessation trials carried out among individuals with DM. 28 29 These trials, which were initiated before the COVID-19 pandemic, in 2018, 28 and after the declaration of the pandemic, in August 2020, 29 did not reach the target sample size and were later terminated due to lack of funding, 28 and following the recall of varenicline which was one element of the study intervention, 29 respectively. Conducting a feasibility study will help estimate the recruitment rate and study uptake, identify potential challenges (along with mitigating factors) and assure the intervention’s acceptability among patients and providers a priori, thus ensuring that the main trial targets can be met before proceeding with a larger, definitive trial.…”
Section: Introductionmentioning
confidence: 99%